1995
DOI: 10.1038/376745a0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the catalytic subunit of protein serine/threonine phosphatase-1

Abstract: The crystal structure of mammalian protein phosphatase-1, complexed with the toxin microcystin and determined at 2.1 A resolution, reveals that it is a metalloenzyme unrelated in architecture to the tyrosine phosphatases. Two metal ions are positioned by a central beta-alpha-beta-alpha-beta scaffold at the active site, from which emanate three surface grooves that are potential binding sites for substrates and inhibitors. The carboxy terminus is positioned at the end of one of the grooves such that regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
816
1
15

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 844 publications
(883 citation statements)
references
References 48 publications
50
816
1
15
Order By: Relevance
“…Further, among the three GSTtagged PP2Ac truncates, PP2Ac (51-270) had the highest phosphatase activity (Fig. 3A), consistent with previous speculation that the catalytic activity of PP2A is located on this segment [20] . In addition, Zn 2+ signifi cantly inhibited the PP2Ac (51-270) activity (Fig.…”
Section: Zinc-induced Pp2a Inactivation Occurs On the Pp2ac (51-270) supporting
confidence: 89%
See 2 more Smart Citations
“…Further, among the three GSTtagged PP2Ac truncates, PP2Ac (51-270) had the highest phosphatase activity (Fig. 3A), consistent with previous speculation that the catalytic activity of PP2A is located on this segment [20] . In addition, Zn 2+ signifi cantly inhibited the PP2Ac (51-270) activity (Fig.…”
Section: Zinc-induced Pp2a Inactivation Occurs On the Pp2ac (51-270) supporting
confidence: 89%
“…To further reveal the underlying mechanism, we cut PP2Ac into several segments and then tested their interactions with Zn 2+ using a Zn 2+ -IDA-agarose affinity binding assay. The crystal structure of the PP2A catalytic subunit is not known, however, based on the threedimensional structure of the PP-1 catalytic subunit, which has a catalytic domain highly homologous with PP2A, the PP2Ac (51-270) segment is thought to cover the catalytic active site and metal coordination center [20] . Furthermore, Wozniak et al reported that the motif of amino-acids 50-270 of PP2Ac contains active site with high affi nity with divalent cations [29] .…”
Section: Pp2amentioning
confidence: 99%
See 1 more Smart Citation
“…PP1 consists of a catalytic subunit (PP1c) associated with various regulatory subunits, forming numerous oligomeric enzymes (Wera and Hemmings, 1995;Campos et al, 1996). PP1c and PP2Ac are 67% homologous and most of the amino acids crucial for the three-dimensional structure of PP1c are conserved in PP2Ac (Goldberg et al, 1995). Although OA inhibited PP1 at low concentrations (o100 nM) in vitro, it failed to inhibit PP1 but not PP2A up to 1 mM in cultured cells (Favre et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…5 Cyanopeptolin SS isolated from a natural cyanobacterial bloom caused death of crustaceans 6 as did oscillapeptin J for Thamnocephalus platyurus. 7 While little is known about the toxicity of cyanopeptolins, the most studied cyanobacterial toxins are the microcystins, which exert their hepatotoxicity through protein phosphatase inhibition 8 and are produced by species of the genera Microcystis, Anabaena, Oscillatoria, Planktothrix, and Nostoc. Microcystins are suspected of countless animal poisonings throughout the globe and also thought to be responsible for a severe incident in Brazil, where several persons died of contaminated water.…”
mentioning
confidence: 99%